In Situ Inorganic Ligand Replenishment Enables Bandgap Stability in Mixed‐Halide Perovskite Quantum Dot Solids. Issue 21 (21st April 2022) - Wang, Ya‐Kun; Singh, Kamalpreet; Li, Jiao‐Yang; Dong, Yitong; Wang, Xue‐Qi; Pina, Joao M.; Yu, You‐Jun; Sabatini, Randy; Liu, Yang; Ma, Dongxin; Liu, Jun; Liu, Zeke; et al.
Abstract: Instability in mixed‐halide perovskites (MHPs) is a key issue limiting perovskite solar cells and light‐emitting diodes (LEDs). One form of instability arises during the processing of MHP quantum dots using an antisolvent to precipitate and purify the dots forming surface traps that lead to decreased luminescence, compromised colloidal stability, and emission broadening. Here, the introduction of inorganic ligands in the antisolvents used in dot purification is reported in order to overcome this problem. MHPs that are colloidally stable for over 1 year at 25 °C and 40% humidity are demonstrated and films that are stable under 100 W cm −2 photoirradiation, 4× longer than the best previously reported MHPs, are reported. In LEDs, the materials enable an EQE of 24.4% (average 22.5 ± 1.3%) and narrow emission (full‐width at half maximum of 30 nm). Sixfold‐enhanced operating stability relative to the most stable prior red perovskite LEDs having external quantum efficiency >20% is reported. Abstract : Bandgap‐stable and efficient CsPbBr x I3− x perovskite light‐emitting diodes (PLEDs) are demonstrated by adopting an in situ inorganic ligand exchange. This strategy enables bandgap‐stable mixed‐halide perovskites with nanocrystal colloidal stability exceeding 1 year at ambient conditions. The PLEDs exhibit an external quantum efficiency (EQE) of 24.4% and sixfold‐enhanced operating stability relative to the most stable prior red perovskite LEDs having EQEs >20%.